SOCIAL PHILOSOPHICAL FOUNDATIONS OF THE DEVELOPMENT OF SCIENCE TECHNOLOGY IN UZBEKISTAN (Western European Journal of Historical Events and Social Science, 2024)
This article explores the social philosophical foundations underlying the development of science and technology in Uzbekistan. It examines historical, cultural, and societal factors that influence scientific and technological progress, and how these elements interplay with government policies and educational frameworks. The study aims to provide a comprehensive understanding of the unique dynamics driving innovation in Uzbekistan